FRI0627 DOES ADDING AN US EXAMINATION OF SHOULDERS, TO A ROUTINE DAS-28 SCORE, IMPROVE ACCURACY OF DISEASE ACTIVITY SCORES AND DISEASE STATUS? RESULTS OF A SINGLE CENTRE PILOT STUDY. (June 2019) - Akram, Qasim; Valor, Lara; Janta, Iustina; Nieto, Juan Carlos; Garcia, Letitia; Serrano, Belen; Pedrosa, Teresa; López-Longo, Francisco J.; Sáez, Indalecio Monteagudo; Naredo, Esperanza
Abstract : Background: The DAS28 forms the mainstay of current RA and other chronic inflammatory arthritis (CIA) [i.e. peripheral spondyloarthritis (SpA)] management in clinical practice. DAS28 has certain limitations. Some joints especially the shoulders are difficult to evaluate correctly using this method. The shoulder is deep and highly affected by rotator cuff tendon lesions either due to degenerative or inflammatory arthritis This structural damage can produce pain and swelling. A swollen shoulder joint can be difficult to palpate by physical examination. Using a clinical approach can be inaccurate to ascertain whether shoulder involvement is actually due to true RA-derived inflammatory activity or other degenerative or structural causes. Objectives: To investigate the added value of adding a US assessment of shoulders to DAS28 scores and on disease activity status, in patients with CIA (RA or peripheral SpA) in either disease remission or low disease states who had shoulder pain. Methods: Patients were recruited prospectively over a 3-month period. Each patient had a standard DAS28 performed followed by a formal physical shoulder examination, of both shoulders, including testing active and passive range of movements. A complete US examination of both shoulders was carried out by a rheumatologist experienced in this technique. All patients were examined using the same real-time US machine (Esaote MyLab Twice) using a linear probe, 3-13 MHz frequency and 57% gain. The original DAS28 was recalculated (i.e. US-modified DAS28) according to the presence/absence of inflammatory findings on shoulder US. Results: Thirty-eight patients [82% females; mean (± SD) age 60.3 (11.96) years] were included. In 33 out of 38 (87% [CI95%: 76-98%]) patients the original DAS28 was greater than the US-modified DAS28. This percentage was significantly greater than 50% (p < 0.001). The mean ± SD reduction of DAS28 in those patients who showed DAS28 decrease was 0.73 ± 0.39 units. Twenty-five patients (65.8%) maintained the same disease activity status with original DAS28 and US-modified DAS28. The remaining 13 (34.2%) patients changed their status: 11 (28.9%) patients moved from low activity to remission while 2 (5.3%) patients moved from low activity to moderate activity. Figure 1 and 2 demonstrate some of the ultrasound findings observed in ourt patient group. Conclusion: This study showed that patients improved their disease activity scores and status after an US assessment of their shoulders. A low percentage increased their disease status after shoulder US which can be also important for local or systemic therapeutic decisions. Based on this study, we suggest that shoulder US can provide valuable additional information to the DAS28 when evaluating disease activity in CIA patients. References: [1] Mierau M, Schoels M, Gonda G, Fuchs J, Aletaha D, Smolen JS. Assessing remission in clinical practice. Rheumatology (Oxford)2007;46: 975-9. [2] Naredo E, Aquado P, De Miguel E, Uson J, Mayordomo L, Gijon-Banos J, Martin-Mola E. Painful shoulder: a comparison of physical examination and ultrasonagraphic findings. Ann Rheum Dis2002; 61:132-6.. [3] Micheroli R, Kyburz D, Ciurea A, Dubs B, Bisig SP, Tamborrini G. Correlation of findings in clinical and high resolution ultrasonography examinations of the painful shoulder. J Ultrason2015; 15: 29–44. Acknowledgement: N/A Disclosure of Interests: Qasim Akram Consultant for: Roche/Chugai, Lara Valor : None declared, Iustina Janta: None declared, Juan Carlos Nieto: None declared, Letitia Garcia: None declared, Belen Serrano: None declared, Teresa Pedrosa: None declared, Francisco J López-Longo: None declared, Indalecio Monteagudo Sáez: None declared, Esperanza Naredo Consultant for: Abbvie, Speakers bureau: AbbVie, Roche, Bristol-Myers Squibb, Pfizer, UCB, Lilly, Novartis, Janssen, and Celgene GmbH